Speaking truths with film evidence, ethics, politics in documentary - Nichols, Bill 1942- (University of California Press, 2016)
"What issues, of both form and content, shape the documentary film? What role does visual evidence play in relation to a documentary's arguments about the world in which we live? Can a documentary be believed, and why or why not? How do documentaries abide by or subvert ethical expectations? Are mockumentaries a form of subversion? In what ways can the documentary be an aesthetic experience and at the same time have political or social impact? And how can such impacts be empirically measured? Pioneering film scholar Bill Nichols investigates the ways in which documentaries strive for accuracy and truthfulness, but simultaneously fabricate a form that shapes reality. Such films may rely on re-enactment to re-create the past, storytelling to provide satisfying narratives, and rhetorical figures such as metaphor and expressive forms such as irony to make a point. In many ways documentaries are a fiction unlike any other. With clarity and passion, Nichols offers close readings of several provocative documentaries including Land without Bread, Restrepo, The Thin Blue Line, The Act of Killing, and Steve Jobs: The Man in the Machine as part of an authoritative examination of the layered approaches and delicate ethical balance demanded of documentary filmmakers"-- Provided by publisher.